Diagnostic Overshadowing: Insidious Neuroregression Mimicking Presentation of Autism Spectrum Disorder. Issue 7 (4th September 2022) - Loo, Kek Khee; Cheng, Jerry; Sarco, Dean; Nyp, Sarah S.
Abstract : CASE: Zac is a 13-year-old boy who presented with his parents to developmental-behavioral pediatrics seeking diagnostic clarity. He was born by vaginal delivery at full term after an uncomplicated pregnancy. Developmental milestones were met at typical ages until he was noted to have language delay and to be hyperactive and impulsive on entering preschool at age 4 years. Although he used some phrases in speech, he often used physical force to take toys from other children, rather than using words. On entering preschool at age 4 years, he was noted to have language delay (i.e., continued use of phrase speech only) and to be hyperactive and impulsive. An evaluation to determine eligibility for an Individualized Education Program (IEP) was completed and found him to have delays in cognition, receptive language, expressive language, social-emotional, and adaptive skills. His fine motor skills were in the low average range, and his gross motor skills were in the average range. He was admitted into an early childhood special education program, and aggressive behavior and hyperactivity decreased in the structured classroom. At age 7 years, Zac was re-evaluated by the school district and found to have moderate intellectual disability (ID). Chromosomal microarray analysis and testing for Fragile X syndrome were normal. He was noted to enjoy interacting with other children and adults, but his play was very immature (e.g., preference for cause/effect toys). He was able to respond appropriately when asked his name and age, but he also frequently demonstrated echolalia. He was also evaluated by his primary care physician and found to meet the criteria for attention-deficit/hyperactivity disorder, combined presentation (ADHD). Treatment with methylphenidate was initiated but discontinued after a brief time because of increased aggressive behaviors. Owing to continued significant tantrums, aggressive tendencies, and inability to communicate his basic needs, Zac was evaluated at a local Regional Center (statewide system for resources and access to services for individuals with developmental disabilities) at age 10 years and found to meet the criteria for autism spectrum disorder (ASD), and previous diagnosis of ID was confirmed. Zac received applied behavior analysis (ABA), but this was discontinued after 1 year because of a combination of a change in the insurance provider and parental perception that the therapy had not been beneficial. Zac became less hyperactive and energetic as he grew older. By the time Zac presented to the developmental-behavioral clinic at age 13 years, he was consistently using approximately 30 single words and was no longer combining words into phrases. He had a long latency in responding to verbal and nonverbal cues and seemed to be quite withdrawn. Physical examination revealed scoliosis and hand tremors while executing fine motor tasks. Seizures were not reported, but neuromotor regression was apparent from the examination and history. Laboratory studies including thyroid-stimulating hormone, free T4, creatine kinase, very-long-chain fatty acids, lactate, pyruvate, urine organic acids, and plasma amino acids were normal. Cranial magnetic resonance imaging demonstrated abnormal T2 hyperintensities in the periventricular and deep cerebral white matter and peridentate cerebellar white matter, consistent with a "tigroid" pattern seen in metachromatic leukodystrophy (MLD) and other white matter neurodegenerative diseases. Arylsulfatase A mutation was detected with an expanded ID/ASD panel, and leukocyte arylsulfatase activity was low, confirming the diagnosis of juvenile-onset MLD. Are there behavioral markers and/or historical caveats that clinicians can use to distinguish between ASD/ID with coexisting ADHD and a neurodegenerative disorder with an insidious onset of regression?